2015
DOI: 10.1016/j.jesf.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic capacity and hematological response to exercise: A study on school-going regularly exercising boys in two different air pollution zones

Abstract: The study findings suggest that air pollution could have negative effects on the hematological profile of boys and longitudinal studies may be carried out for assessing its clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…However, a higher concentration of white blood cells was found after the subjects engaged in physical activity at ITB sport venue. This result is in line with previous research which states that individuals who do physical activities with lower air pollution have a lower number of white blood cell than individuals who do it at a higher air pollution level (Das & Chatterjee, 2015;Jacobs et al, 2010;Kargarfard et al, 2011;Margolis, Manson, & Greenland, 2005). The increase of white blood cells, after performing physical activity in an environment exposed to a high PM2.5, might be due to the effect of PM2.5 which could damage the tissue of the body so that the body produces more antibodies in response to a high expo-sure to PM2.5.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, a higher concentration of white blood cells was found after the subjects engaged in physical activity at ITB sport venue. This result is in line with previous research which states that individuals who do physical activities with lower air pollution have a lower number of white blood cell than individuals who do it at a higher air pollution level (Das & Chatterjee, 2015;Jacobs et al, 2010;Kargarfard et al, 2011;Margolis, Manson, & Greenland, 2005). The increase of white blood cells, after performing physical activity in an environment exposed to a high PM2.5, might be due to the effect of PM2.5 which could damage the tissue of the body so that the body produces more antibodies in response to a high expo-sure to PM2.5.…”
Section: Discussionsupporting
confidence: 93%
“…Hematological parameters suggested that the significantly lower value of hemoglobin after exercise in high-polluted air might be due to a slight increase of blood volume after an exposure to higher levels of air pollutants. The results of our study are in line with previous studies which state that there was a decrease in hemoglobin after carrying out physical activity in a high air pollution condition (Das & Chatterjee, 2015;Davidson & Penney, 1988;Kargarfard et al, 2011). In addition, this study also found an increase of white blood cells in research subjects after doing physical activity in both public sport venues.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With extra blood in the lungs, less is available to do the work of blood throughout the body, a condition apparent as reduced hemoglobin (Seaton et al 1999). While Kargarfard et al (2015) find no link between pollution and hemoglobin, several other studies have documented a short-term link between exposure to air pollution and decreased hemoglobin (Das and Chatterjee 2015;Nikolic et al 2008, Poursafa et al 2011, Seaton et al 1999). However, we are aware of no work that examines the pollution-hemoglobin relationship in the long term, and the most recent article we found, Das and Chatterjee (2015) calls for more longitudinal work on the subject.…”
Section: Methodsmentioning
confidence: 93%